(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2017)
Pyrethroids are greatly in use these days therefore can contaminate ecosystem and living forms therein. Present investigation reveals the toxic potential of two type-II pyrethroids, cypermethrin and beta-cyfluthrin at the level of giant cell formation through histological examination in liver of albino rats. It has been observed that both these experimental compounds cause giant cell formation in the liver of treated animals with beta-cyfluthrin having an edge over cypermethrin, probably due to difference in their chemical structures.